2001
DOI: 10.1300/j087v36n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Parental Divorce and the Quality of Adult Sibling Relationships

Abstract: Two theoretical approaches make opposite predictions concerning the effects of parental divorce on sibling relationship quality. From a social learning perspective, via modeling the individual learns negative patterns of interpersonal relations through the experience of parental conflict and divorce, which negatively affects relationship quality throughout the life span. A social support approach argues that sibling relationships may serve as a buffer to shield the individual from negative interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 42 publications
2
49
2
5
Order By: Relevance
“…Moreover, research on adults suggests that this negative effect persists in adulthood. Samples of young adults have shown that siblings of divorced parents are less close and supportive than siblings from intact families (Milevsky, 2004;Riggio, 2001), and findings based on samples of older adults have shown such negative effects of parental divorce in cases of sibling conflict (Panish & Stricker, 2001). Given that most evidence is in the direction of a negative effect, we expect that siblings of divorced parents have less contact, more conflict, and lower relationship quality than do siblings from intact families.…”
Section: Journal Of Family Issuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, research on adults suggests that this negative effect persists in adulthood. Samples of young adults have shown that siblings of divorced parents are less close and supportive than siblings from intact families (Milevsky, 2004;Riggio, 2001), and findings based on samples of older adults have shown such negative effects of parental divorce in cases of sibling conflict (Panish & Stricker, 2001). Given that most evidence is in the direction of a negative effect, we expect that siblings of divorced parents have less contact, more conflict, and lower relationship quality than do siblings from intact families.…”
Section: Journal Of Family Issuesmentioning
confidence: 96%
“…The divorce literature has paid relatively little attention to the effect of parental divorce on these types of nuclear family ties. Only a few studies have examined how parental divorce affects sibling relationships (e.g., Amato, 1987;Riggio, 2001). This lack of attention is surprising and unfortunate.…”
mentioning
confidence: 99%
“…Similarly, it has been observed that adolescents from single-parent families are likely to experience more negative sibling relationships than those in two-parent families (Drapeau, Samson & Saint-Jacques, 1999:35;Hetherington, 1993:41). According to Frank (2007:107), the three empirical studies (Milevsky, 2004;Panish & Stricker, 2001;Riggio, 2001) conducted on adult sibling relationships thus far found that "young adults from divorced families have a lower quality of sibling relations", even though Riggio (2001) found this to be true "only if divorce had occurred beyond the age of eight." Therefore, additional research is necessary to contribute towards knowledge in this regard.…”
Section: Sub-theme: Animosity Among Adolescents and Their Siblingsmentioning
confidence: 99%
“…A growing body of literature has documented the importance of family relationships as an important mechanism for both social support and emotional health (Cohen, 2004;Ross, 1995). As suggested earlier, parental divorceregardless of the age at which it is experienced-can have lasting effects on familial relationships, including parent-child and sibling relationships (Riggio, 2001). The initial consequences of parental divorce include higher levels of conflict across the family members, as well as lowered levels of contact (Noller, Feeney, Sheehan, & Darlington, 2008;Shapiro & Cooney, 2007).…”
Section: Effects Of Parental Divorcementioning
confidence: 99%
“…Most of these have focused on outcomes associated with young children (Allison & Furstenberg, 1989;Amato, 1996;Bouchard, Lachance-Grzela, & Goguen, 2008;Kaufman & Uhlenber, 1998;McCabe, 1997;Pett, Lang, & Gander, 1992;Riggio, 2001Riggio, , 2004, but far fewer studies have focused on the consequences of parental divorce for those who experienced the dissolution of their parents' marriage as adult children (Aquilino, 1994;Cherlin, 1998;Shapiro, 2003). These studies attempt to document the consequences that parental marital dissolution can create for children-based on the life stage in which children experience parental divorce, but no research that we are aware of has directly compared the experiences of young and adult children of parental divorce.…”
Section: The Timing Of Divorcementioning
confidence: 99%